PLUMBING THE BRAIN DRAIN OF SOUTH AFRICAN SOCIAL WORKERS MIGRATING TO THE UK: CHALLENGES FOR SOCIAL SERVICE PROVIDERS - Engelbrecht, Lambert K (Social Work/Maatskaplike Werk, 2006)
This article reports research that was undertaken to uncover generalisations pertaining to the migration of South African social workers to the United Kingdom (UK). The intention was to identify challenges for the future contribution of social service providers in South African if local social workers are to be retained in the country. In the South African social work milieu it is recognised formally and informally that a significant number of social workers migrated to the UK during the first decade after democracy. This can be classified as a distinct brain drain of social workers, which has a vital impact on social service delivery and social development (Business Day, 2005; Cape Times, 2004; Louw, 2003:xv-xvi; Herald, 2005). However, verifiable data on the brain drain phenomenon in social work are not available (Business Day, 2005). With reference to Saravia and Miranda’s (2004) use of the metaphor, a plumbing of the South African social workers’ brain drain to the UK is thus needed. This plumbing is effected by describing the research design and methodology, sketching the background for the survey, reporting the survey results, and identifying challenges for social service providers.